2010
DOI: 10.1007/s10147-010-0080-7
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial carcinoma: better prognosis for asymptomatic recurrences than for symptomatic cases found by routine follow-up

Abstract: A better prognosis after recurrence was demonstrated in cases that were asymptomatic at the time of recurrence detection than in those in which the tumor was symptomatic. This finding implies that, after the initial surgical resection, intensive follow-up intervention looking for asymptomatic recurrences may significantly improve the prognosis of endometrial carcinoma patients. A further in-depth prospective study is required to establish a standard strategy of follow-up care for endometrial cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
(25 reference statements)
2
8
4
1
Order By: Relevance
“…Women diagnosed at a pre-scheduled visit due to symptoms had a higher educational level and more often high-risk disease compared to symptomatic women diagnosed at regular follow-up. Previous studies have used retrospectively collected survival data to conclude on the efficacy and justification of follow-up visits [3,4,[15][16][17][18][19][20][21]. In addition to the present study, a minority of the studies [3,4] found a better survival of women with asymptomatic recurrence and it seems tempting to conclude that follow-up visits improve survival.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Women diagnosed at a pre-scheduled visit due to symptoms had a higher educational level and more often high-risk disease compared to symptomatic women diagnosed at regular follow-up. Previous studies have used retrospectively collected survival data to conclude on the efficacy and justification of follow-up visits [3,4,[15][16][17][18][19][20][21]. In addition to the present study, a minority of the studies [3,4] found a better survival of women with asymptomatic recurrence and it seems tempting to conclude that follow-up visits improve survival.…”
Section: Discussioncontrasting
confidence: 44%
“…Most of the studies conclude that the majority [70% (95% CI 65-75)] of recurrences are symptomatic [2], and the survival rates of asymptomatic and symptomatic cases are similar thus challenging the current follow-up strategy [1,2]. However, a few studies demonstrated a better survival in asymptomatic cases [3,4] which may be interpreted as a need for regular follow-up.…”
mentioning
confidence: 99%
“…A study from 2010 of 271 endometrial cancers indicates that this could be the case, because the authors found an increase in progression-free survival in asymptomatic cases found at routine follow-up compared to symptomatic cases, this being especially true in patients who underwent chemotherapy as their adjuvant therapy. 24 In the present study, 6.3% of low and 22% of intermediate risk recurred. Of these, 40% were diagnosed more than 2 years and 13% more than 5 years after the primary surgery.…”
Section: Discussionsupporting
confidence: 46%
“…The commonest type, which is the endometrioid endometrial cancer (EEC) or type I, has an underlying endometrial hyperplasia, and low-grade and minimal myometrial invasion. EEC (4). Much of the ongoing research still focuses on identifying biomarkers for early detection, understanding the pathophysiology, and monitoring the course of treatments.…”
Section: Introductionmentioning
confidence: 99%